PENGARUH PULL DAN PUSH MOTIVATION TERHADAP REVISIT INTENTION DIMEDIASI OLEH SATISFACTION PADA WISATAWAN PANTAI SIKABAU KABUPATEN PASAMAN BARAT - Rika Rahmadina; Eri Besra; Dessy Kurnia Sari (Halu Oleo University, 2025)
The study aims to examine the effect of pull and push motivation on revisit intention mediated by satisfaction for Sikabau beach tourists in Pasaman Barat Regency. Respondents were selected using a purposive random sampling technique with a total of 200 samples consisting of individuals who had visited Sikabau Beach at least once. The data is obtained by distributing online questionnaires to respondents and analyzed using SmartPLS. The data analysis method uses structural equation modelling with partial least squares (SEM-PLS). The result showed that push motivation has a significant effect on revisit intention, while pull motivation shows an insignificant effect on revisit intention. Pull motivation, push motivation and satisfaction have significant effects on revisit intention. Satisfaction is able to partially mediate the relationship between pull motivation and revisit intention, while push motivation and revisit intention are fully mediated by satisfaction.